Obesity Associated with Low Lean Mass and Low Bone Density Has Higher Impact on General Health in Middle-Aged and Older Adults - Natasha A. G. de França; Barbara S. E. Peters; Elizabete A. dos Santos; Marcela M. S. Lima; Regina M. Fisberg; Ligia Araújo Martini (Hindawi Limited, 2020)
It is believed that the phenomenon of simultaneous changes in body composition could have a higher negative impact on general health. Thus, we aimed to investigate the prevalence of concomitant body composition disturbances and evaluate the association with dietary intake, sedentary behaviour, muscle strength, and performance. This is a cross-sectional study with 218 community-dwelling adults, aged 63 (59-69) years, both sexes (52% female) recruited from the Health Survey of the City of São Paulo. Assessments include appendicular lean mass (LM), fat mass and bone mineral density (BMD) by DXA, grip strength, time spent sitting, and dietary intake. Subjects were clustered into 8 groups: (1) normal, (2) osteopenia (OP), (3) low LM, (4) obesity, (5) OP + low LM, (6) obesity + OP, (7) obesity + low LM, and (8) obesity + OP + low LM. Statistical analyses include ANCOVA, the chi-square test, and linear regression models. 52 (23%) individuals presented obesity associated with another body composition change, with 14 (6%) having the combination of the 3 conditions (obesity + OP + low LM). All groups with obesity showed lower protein intake (p≤0.001); however, those with obesity or obesity + low LM spent more time in a sitting position (p=0.002), and the group with obesity + OP + low LM had the lowest grip strength. The combination of obesity with low LM and OP presented the aggravating factor of being associated with lower grip strength. In a context of demographic and nutrition transition, the findings represent a demand for longitudinal investigations.